CORRELATION BETWEEN VITAMIN D DEFICIENCY AND LOW BODY HEIGHT - Panji Sananta; Aristoteles Aristoteles; Fauzan Yusman; Satrio Bangun Negoro; Muhammad Hilman Bimadi; Felix Cendikiawan (Journal of Community Health and Preventive Medicine, 2021)
The average height of the Indonesians population has increased a few centimeters for the last 50 years, although Indonesians are short. However, a secular trend in height was still unclear. Currently, the Indonesians adult population is averagely shorter than the modern World Health Organization (WHO) reference males and females. Thus, when comparing the height of Indonesian children with several growth measurements, a significant portion of the children is below the critical limit. This review aimed to discuss the correlation between deficiency vitamin D and low body height